Introducing Technical & Vocational Education and Training (TVET) in the Secondary Schools in Nepal: Opportunities and Challenges - Kanel, Chet Nath (Journal of Training and Development, 2015)
Nepal's education sector is striving for producing quality human resources for the country. However, due to lack of appropriate policy, priority and curricula, the efforts have been less effective. Education sector has also been a subject of criticism due to mismanagement of the 'products' and the industry demands. Taking these matters into considerations, Government of Nepal is trying to introduce the TVET in secondary education (9-12) system as a pilot-basis. This article has explored some of the critical issues associated with the intention of introducing TVET, its demand and supply-sides debates, challenges as well as opportunities in expanding TVET in Nepalese secondary education system. Literature review, some expert-interviews and reflection of personal experiences are the key methods of information generation for this article. The main conclusion of this article is that the TVET system in Nepal has very high demand to produce the required and quality human resources in Nepal. There are ample opportunities in introducing the expanding of TVET in Nepal. However, key learning from 99-piloted schools should be main basis to take further steps visualizing the feasibility, employability and sustainability from students, schools, and schools' perspectives. Even after the School Sector Reform Program (SSRP), the initiative of introducing TVET in all secondary schools of Nepal should continue. DOI: http://dx.doi.org/10.3126/jtd.v1i0.13083 Journal of Training and Development Vol.1 2015: 3-8